H−,R−and L−cross-sections of the infinite symmetric inverse semigroup ISX - Pyekhtyeryev, V. (Algebra and Discrete Mathematics, 2005)
All H−,R− and L−cross-sections of the infinite
symmetric inverse semigroup ISX are described.